Impact of IDH1 and IDH2 mutational subgroups in AML patients after allogeneic stem cell transplantation - Kunadt, Désirée; Krämer, Alwin; Müller-Tidow, Carsten; Bornhäuser, Martin (Journal of hematology & oncology, 2022)
The role of allogeneic hematopoietic cell transplantation (alloHCT) in acute myeloid leukemia (AML) with mutated IDH1/2 has not been defined. Therefore, we analyzed a large cohort of 3234 AML patients in first complete remission (CR1) undergoing alloHCT or conventional chemo-consolidation and investigated outcome in respect to IDH1/2 mutational subgroups (IDH1 R132C, R132H and IDH2 R140Q, R172K).